Mesoscopic simulation of thermo-mechanical behaviors in concrete under frost action. (30th December 2017) - Zhou, Wei; Zhao, Cheng; Liu, Xinghong; Chang, Xiaolin; Feng, Chuqiao
Highlights: A comprehensive coupled model is proposed to study freeze-thaw process in concrete. The damage resulting from many freeze-thaw cycles is included in the coupled model. The freeze-thaw behaviors of concrete are simulated at mesoscale by using the FEM. The roles of some meso-structure parameters on freeze-thaw behaviors are discussed. Abstract: This work presents a comprehensive coupled thermal-hydro-mechanical model to simulate both freezing and thawing processes in concrete while considering liquid overpressure and the deterioration of material characteristics. The proposed model is validated through a comparison with available experimental data obtained from the literature. A random polygons meso-structure of concrete is established, within which the mortar, interfacial transition zones (ITZs) and aggregates are distinctly represented. Mesoscopic finite element simulations are conducted to assess the effects of the permeability of mortar and the ITZs, the thermal expansion property of the ITZs, aggregate volume fraction and aggregate gradation. The outcomes indicate that the permeability of the ITZs and the aggregate volume fraction play a significant role in the freezing/thawing behavior of concrete. Furthermore, the impacts of the thermal expansion property of ITZs and the aggregate gradation should not be overlooked.